Some methodological aspects of the controversy between mainstream economics and institutionalism - Peter Galbács (Duke University, Center for the History of Political Economy (CHOPE), 2017)
Mainstream economics has been running the gauntlet of adverse criticism for decades. These critiques claim as a message of central importance that mainstream economics has lost its relevance as for understanding reality. By making a brief comparison between the methodological strategies of the main stream and institutional economics I suggest that the firm demarcation between the streams stems from the difference between their methodologies. Its peculiar interest directed mainstream economics to take a unique methodological path and consequently the adherents have not been able to be on the lookout for certain facets of socio-economic reality. However, the chosen path, the axiomatic-deductive strategy proved to be an appropriate method for identifying economic laws. This claim is justified even by some recent efforts of new institutional economics. In order to support the conversation between the schools I highlight some causes that currently make it impossible to start a rational discourse.
Keywords: B13; B15; B41; C12; 330; mainstream economics; institutional economics; methodology of economics; isolation; homo oeconomicus